Dark tourism and pilgrimage - Olsen, Daniel H.; Korstanje, Maximiliano (CABI Religious tourism and pilgrimage series, 2020)
This volume is an eclectic multidisciplinary collection of essays related to the interconnections between dark tourism and pilgrimage travel. It focuses on dark tourism sites as pilgrimage destinations, dark tourists as pilgrims, and pilgrimage as a form of dark tourism. Theories and histories of dark tourism and pilgrimage are covered, as well as aspects of the visitor experience, including tourists' motivations and emotional responses, and social aspects, among others. The book has 22 chapters and a subject index.